Tanggung Jawab Orang Tua terhadap Pendidikan Akhlak Anak dalam Perspektif Al-Qur’an - Achmad Junaedi Sitika; Ine Nirmala (Al Hikmah: Indonesian Journal of Early Childhood Islamic Education (IJECIE), 2017)
Parent is the first teacher for children that should have designed the pattern and methods of parenting in educating their children, since waiting for the birth of a child, even before marriage. This research is motivated by a big challenge in educating children today which is so influenced by fast and many information that can exert a bad influence created by the environment of modernity that lacks religious values. The purpose of this study is to know the responsibility of parents in moral education of children based on Al-Quran, At-Tahrim verse 6. Using qualitative methods, searching and collecting data through library research. Responsibility of parent in moral education of children based on Al-Qur'an, At-Tahrim verse: 6 that is the importance of obedience to Allah, always remembering Him in zikr, and forbid children from disgraceful acts, by with educating and teaching the children about tauhid and moral valuess, especially educating how to perform and establish prayers, because with prayers, it can prevent people from a bad and worst behaviour.